Sleep in Emergency Services Workers: What Do We Know and Why Does It Matter?. Issue Volume 34:Issue s1(2019) (May 2019) - Ferguson, Sally; Aisbett, Brad; Wolkow, Alexander; Jay, Sarah; Ridgers, Nicola; Vincent, Grace
Abstract : Introduction: Emergency service workers perform physical work while being subjected to multiple stressors and adverse, volatile working environments for extended periods. Recent research has highlighted sleep as a significant and potentially modifiable factor impacting operational performance. Aim: This presentation would (a) examine the existing literature on emergency service workers' sleep quantity and quality during operations, (b) synthesize the operational and environmental factors that impact sleep (e.g., shift start times, shift length, sleeping location, smoke, noise, heat), and (c) assess how sleep impacts aspects of emergency service workers' health and safety, including mental and physical health and performance. Methods: This presentation would be based on a narrative review conducted by the authors which used a systematic search strategy of health-related databases. Articles that were not relevant, duplicate or from non-peer-reviewed sources were excluded. Results: Sleep is restricted during emergency service deployments, particularly when shifts have early start times, are long duration, and/or when sleeping in temporary accommodation (e.g., tents, vehicles). Shortened sleep impairs cognitive but not physical performance under simulated emergency services conditions. Discussion: Depending on the organization and jurisdiction, these findings warrant re-evaluation of existing policies, formalization of beneficial but currently ad-hoc practice, or provide support for current procedures. Work shifts should be structured, wherever possible, to provide regular and sufficient recovery opportunities (rest during and sleep between shifts), especially in dangerous working environments where fatigue-related errors have more severe consequences. For agencies to continue to defend local communities against natural hazards, strategies should be implemented to improve and manage emergency service workers sleep and reduce any adverse impacts on work.